Growth and yield responses of cowpea to plant densities in two agro-ecologies in Northern Nigeria: a yield compensation mechanism - Odesina, I.S.; Utoblo, O.; Oyebode, G.O.; Ongom, P.O.; Boukar, O.; Namo, O.A.T. (MDPI, 2025)
Low plant stands at early crop establishment contribute to yield reduction in legumes. Gap-filling has been suggested as a mechanism to mitigate these losses. There is, however, limited understanding of a yield-compensation mechanism in the cowpea. This study aimed to investigate the mechanism of yield-compensation in some accessions of cowpeas at Minjibir and Shika in Northern Nigeria. The experiment was laid out in a split plot fitted into a randomized complete block design in three replicates. The main plot consisted of four plant densities (33,333; 66,666; 99,999; 133,333 plants ha−1) while the subplots consisted of six cowpea accessions (IT89KD-288, IT93K-452-1, IT99K-537-1-1, IT98K-205-8, IT08K-150-27, and DANILA). Results showed that plant density and environment affected grain yield. Total grain yield increased with increasing plant density and was higher at Minjibir than at Shika. The highest total grain yield of 1793.3 kg ha−1 was observed in the accession DANILA at 99,999 plants ha−1, while the lowest (1100 kg ha−1) was observed in the accession IT98K-205-8 at 33,333 plants ha−1. Leaf area index, stand count at harvest, and intercepted photosynthetically active radiation were positively correlated with total grain yield at both locations, suggesting that these traits could be considered for cowpea improvement. Cowpea growers and breeders could consider the erect (IT93K-452-1 and IT98K-205-8) and semi-erect accessions (IT99K-573-1-1 and IT08K-150-27) for cultivation at 133,333 plants ha−1. Prostrate accessions (IT89KD-288 and DANILA) could be planted at 99,999 plants ha−1 at Minjibir. The accessions IT93K-452-1-1, IT98-205-8, IT99K-573-1-1, and IT08K-150-27 could be considered for cultivation at Shika irrespective of plant density.